SIX NEW SPECIES OF TETRAPTERYS (MALPIGHIACEAE) - Anderson, C. (Edinburgh Journal of Botany, 2016)
Six new species of the Neotropical genus Tetrapterys (Malpighiaceae) are described and illustrated: T. amazonica C.E.Anderson (Brazil, Colombia and Peru), T. andersonii C.E.Anderson (Mexico), T. callejasii W.R.Anderson (Colombia), T. molinae W.R.Anderson (Honduras), T. rzedowskii W.R.Anderson (Mexico) and T. steyermarkii W.R.Anderson (Colombia and Venezuela). All have 4(–6)-flowered umbels as the ultimate inflorescence units, glabrous yellow petals, and samaras with a small dorsal wing in addition to the four large lateral wings.